Case report on placenta accreta presenting obstetric emergency - Sharma, Vishal; Kaur, Jashandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Placenta accreta is a potentially life-threatening obstetric condition that requires a multidisciplinary approach to management. As the incidence of Caesarean have increased, Placenta accreta also has increased and considered as an important cause of maternal and fetal/neonatal morbidity and mortality. Although multiple caesarean deliveries are at the largest risk factor for the placenta accreta, increasing maternal age and parity, as well as other uterine surgeries are also important. In Patient at risk for accreta, obstetrical ultrasonography performed by an experienced provider should be obtained. A multidisciplinary team in a centre with expertise in managing placenta accreta should care for case of suspected accreta.